Influence of Operation and Maintenance to Utilization of Sanitation Facilities by Women in Mukuru Kwa Reuben in Nairobi City County - Kariuki, Teresia Mucia; Dorothy Kagendo; Maryjoy Kaimuri, (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Accessing basic sanitation services is still a challenge in slums and sanitation needs of women at times remain unmet. This study aimed at assessing the effect of the operation and maintenance to the utilization of sanitation facilities by women in Mukuru kwa Reuben, Nairobi city county Kenya. The study was premised on the Health Action Process Approach and targeted all women aged 18 and above who consented and were the primary users of sanitation facilities and resident in Mukuru Kwa Reuben community. Sample for the study was 395 gotten using the Yamane formula. Sampling was by use of clustered and simple random sampling for women in households. The main instruments of data collection were questionnaire, focus group discussions, and observation check list. Quantitative data was analyzed for descriptive and inferential statistics and findings presented in form of percentages, means, and frequencies then presented in tables. Qualitative data was thematically analyzed and presented in form of narratives. Results from the analysis showed that majority of the respondents (54.2%) were aged 31-40 years, married (41.0%), attained primary level education (49.0%) employed and (35.4%) unemployed. The most common sanitation facility was container based (51.0%). Correlation results showed that Cleaning frequency (r=-0.672, p=0.000), had a strong positive association with utilization, Exhausting frequency (r=0.319, p=0.001), had also positive and significant interconnection with utilization, and Repairing (r=0.191, p=0.000), had a weak positive but significant association with utilization, Daily Inspection (r=0.364, p=0.000), had positive relation with utilization, This study highlights persistent challenges in slums, particularly for women's access to sanitation. Operation and maintenance aspects especially cleaning frequency significantly influence facility utilization in Mukuru Kwa Reuben. Hence emphasizing the need for regular and effective cleaning of facilities in order to promote the utilization of sanitation facilities.